Chagas and health promotion: dialogue inspired by the Curitiba Statement - Sanmartino, Mariana (2019)
With the objective of providing an insightful analysis of Chagas disease in the world, the authors share their collective reflections about the current situation of this public health problem in: rural environments of Latin America; urban environments of endemic and non-endemic areas everywhere; and, at a global level. A perspective based on the ‘Democracy and Health Promotion’ axis allowed the development of an innovative update about Chagas disease as a model of a complex socio-environmental health problem, with a key set of elements that goes beyond biomedical aspects. The authors created a dialogue between the fundamental elements of the Curitiba Statement on Health Promotion and Equity and crucial aspects of a reflection on the reality of Chagas disease today that at the same time challenges the different actors involved. With that reference, the call to promote a ‘critical analysis of viabilities and opportunities for action, considering the potentialities and barriers imposed by the complexity of social movements in the present context of recedes and the loss of rights’ was emphasized repeatedly. Finally, on the occasion of the recent creation of the Technical Group on Information, Education and Communication to control Chagas disease, WHO Department of Control of Neglected Tropical Diseases, the authors share reflections to propose an inclusive and transformative approach of health promotion what we hope is a new horizon for people affected, directly and indirectly, by Chagas disease.